2016
DOI: 10.3389/fphys.2016.00627
|View full text |Cite
|
Sign up to set email alerts
|

No Critical Peripheral Fatigue Threshold during Intermittent Isometric Time to Task Failure Test with the Knee Extensors

Abstract: It has been proposed that group III and IV muscle afferents provide inhibitory feedback from locomotor muscles to the central nervous system, setting an absolute threshold for the development of peripheral fatigue during exercise. The aim of this study was to test the validity of this theory. Thus, we asked whether the level of developed peripheral fatigue would differ when two consecutive exercise trials were completed to task failure. Ten trained sport students performed two exercise trials to task failure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
(109 reference statements)
4
12
1
Order By: Relevance
“…Studies using protocols more comparable to the present study found that the level of peripheral fatigue at task failure is higher following a pre-fatiguing isometric trial of the same muscle group using either intermittent [15] or sustained [23] contractions. Surprisingly, evoked peak forces for SS, PS100 and tetanus did not change significantly from task failure in the first compared to the second trial (Table 1), and thus contrast with the results from the first experimental visit [15], and with the reduction in evoked peak force from the first to the third trial. We believe that this might have happened because two of the ten subjects seemed to lose motivation and "give up" exercise prematurely during the second trial (subjects 1 and 3, Figure 4).…”
Section: Neuromuscular Activation and Peripheral Fatigue At Task Failuresupporting
confidence: 63%
See 4 more Smart Citations
“…Studies using protocols more comparable to the present study found that the level of peripheral fatigue at task failure is higher following a pre-fatiguing isometric trial of the same muscle group using either intermittent [15] or sustained [23] contractions. Surprisingly, evoked peak forces for SS, PS100 and tetanus did not change significantly from task failure in the first compared to the second trial (Table 1), and thus contrast with the results from the first experimental visit [15], and with the reduction in evoked peak force from the first to the third trial. We believe that this might have happened because two of the ten subjects seemed to lose motivation and "give up" exercise prematurely during the second trial (subjects 1 and 3, Figure 4).…”
Section: Neuromuscular Activation and Peripheral Fatigue At Task Failuresupporting
confidence: 63%
“…RMS during MVCs was divided by the M-wave peak to peak amplitude of the following SS response to estimate neuromuscular activation (RMS•M -1 ) [5]. In several studies RMS•M -1 has been used to calculate neuromuscular activation [14,15,26], whereas RMS has been used to calculate central motor drive [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations